Enhanced sensing capabilities of UV–visible p-n and p-i-n photodiodes using unique layer and contact configurations - Ahmed Ali Alarabi; Osman Çiçek; Hasan Makara; Fatih Ünal; Merve Zurnacı; Şemsettin Altındal (Engineering Science and Technology, an International Journal)
This paper focuses on the ultraviolet–visible (UV–vis) light response of the p-n and p-i-n vertical self-powered photodiodes (PDs) based on p-PMItz/n-Si, p-PMItz/n-4HSiC and p-PMItz/i-SiO2/n-Si Heterojunctions. The PDs, referred to as Device A-B-C-D-E and F according to the modified structures, were produced to increase the sensing capacity using distinct anode contacts. The basic fundamental parameters were recorded using the I-V data of PDs with thermionic emission theory (TE) and Ohm’s law. The results showed that, in line with the literature, the potential barrier height (ФBo) decreased, and the ideality factor (n) increased with increasing illumination intensity. Additionally, the voltage-dependent series resistances (Rs) of PDs in the dark and under different UV–vis light intensities were determined using Ohm’s laws. It was recorded that Rs decreased as light intensity increased. On the other hand, the photosensitivity properties of PDs in UV–vis intensities depending on the voltage were investigated. The photosensitivity of the fabricated Device B reached a maximum of 4.05x104 at short circuit voltage (Vsc = 0 V). In contrast, when self-powered, the short-circuit voltage (Voc) showed better photosensitivity (with a minimum of 0.058). Additionally, the specific detectivity (D*) and the responsivity (R) of the PDs were calculated. According to the literature, the R and D* decreased with increasing power density at zero-bias voltage. Also, the R of Device B is higher, and D* is lower than other devices. The linear dynamic range (LDR) of Device A reaches ∼ 92 dB with maximum (Vbias = 0 V) while the dark current is 0.038 nA with minimum (in self-powered mode). Device B is considered suitable for the PDs (in self-powered mode) among other devices.